Malignant mammary tumor in female dogs: environmental contaminants - Andrade, Fabio H. E.; Figueiroa, Fernanda C. [UNESP]; Bersano, Paulo R. O. [UNESP]; Bissacot, Denise Z. [UNESP]; Rocha, Noeme S. [UNESP] (Biomed Central Ltd., 2010)
Mammary tumors of female dogs have greatly increased in recent years, thus demanding rapid diagnosis and effective treatment in order to determine the animal survival. There is considerable scientific interest in the possible role of environmental contaminants in the etiology of mammary tumors, specifically in relation to synthetic chemical substances released into the environment to which living beings are either directly or indirectly exposed. In this study, the presence of pyrethroid insecticide was observed in adjacent adipose tissue of canine mammary tumor. High Precision Liquid Chromatography - HPLC was adapted to detect and identify environmental contaminants in adipose tissue adjacent to malignant mammary tumor in nine female dogs, without predilection for breed or age. After surgery, masses were carefully examined for malignant neoplastic lesions. Five grams of adipose tissue adjacent to the tumor were collected to detect of environmental contaminants. The identified pyrethroids were allethrin, cyhalothrin, cypermethrin, deltamethrin and tetramethrin, with a contamination level of 33.3%. Histopathology demonstrated six female dogs (66.7%) as having complex carcinoma and three (33.3%) with simple carcinoma. From these tumors, seven (77.8%) presented aggressiveness degree III and two (22.2%) degree I. Five tumors were positive for estrogen receptors in immunohistochemical analysis. The contamination level was observed in more aggressive tumors. This was the first report in which the level of environmental contaminants could be detected in adipose tissue of female dogs with malignant mammary tumor, by HPLC. Results suggest the possible involvement of pyrethroid in the canine mammary tumor carcinogenesis. Hence, the dog may be used as a sentinel animal for human breast cancer, since human beings share the same environment and basically have the same eating habits.